Development of Professional Competencies of Future Preschool Teachers in Preschool Education Institutions through Digital Technologies: Foreign Research and Pedagogical Discourse - Kobyletska, Oksana (Педагогічна Академія: наукові записки, 2026)
Objective. The purpose of the article is a theoretical analysis of foreign scientific and pedagogical discourse on the development of professional competencies of future educators of preschool educational institutions using digital technologies and the identification of modern conceptual approaches and trends in the formation of their digital competence in the international educational space. Methods. The study employs the methods of theoretical analysis, generalization and systematization of foreign scientific sources dedicated to digital transformation in education, professional training of future educators and the development of their digital competence. Results. The analysis demonstrates that foreign scientific and pedagogical discourse treats digital competence as an integrative component of the professional training of a future educator. The study identifies leading approaches to the professional training of future educators of preschool educational institutions. It has been established that digital technologies are considered not only as tools for organizing education, but also as factors that transform the content and methods of professional training. Emphasis is placed on developing the ability of future educators to design a safe digital educational environment, effectively adapt digital content to the developmental and age characteristics of preschool children, and ensure methodologically appropriate integration of technological tools into the educational process in accordance with pedagogical goals. The results also show that foreign studies increasingly emphasize the continuous professional development of educators, digital ethics, and the creation of a favorable digital educational environment. Conclusions. The study concludes that the development of professional competencies of future preschool educators using digital technologies is a complex and multidimensional process that requires the integration of pedagogical, technological, communicative, and ethical components.